American mother : the true story of a troubled family, motherhood, and the cyanide murders that shook the world - Olsen, Gregg; Olsen, Gregg (New York : Grand Central Publishing, 2022)
At 5.02 pm on June 5, 1986, an emergency call came into the local sheriff's office in the small town of Auburn, Washington State. A distressed housewife, Stella Nickell, said her husband Bruce was having a seizure. Officers rushed to the Nickell's mobile home, to find Stella standing frozen at the door Bruce was on the floor fighting for his life. As Stella became the beneficiary of over"--Publisher's description
"Previously published as Bitter Almonds"--Cover.
Keywords: Nickell, Bruce, -- 1934-1986.; Nickell, Stella Maudine; Nickell, Bruce, -- 1934-1986.; Nickell, Stella Maudine; Murder -- Washington (State) -- Seattle -- Case studies; Victims of crimes -- Washington (State) -- King County; Murder; Victims of crimes; Washington (State) -- King County; Washington (State) -- Seattle; Case studies; True crime stories; Print books; True crime stories; Case studies